2023
DOI: 10.1002/anie.202217173
|View full text |Cite
|
Sign up to set email alerts
|

Structural Fusion Yields Guest Acceptors that Enable Ternary Organic Solar Cells with 18.77 % Efficiency

Abstract: The design and selection of a suitable guest acceptor are particularly important for improving the photovoltaic performance of ternary organic solar cells (OSCs). Herein, we designed and successfully synthesized two asymmetric silicon–oxygen bridged guest acceptors, which featured distinct blue‐shifted absorption, upshifted lowest unoccupied molecular orbital energy levels, and larger dipole moments than symmetric silicon–oxygen‐bridged acceptor. Ternary devices with the incorporation of 14.2 wt % these two as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…The cascaded energy level alignments were favorable for efficient charge transfer at the D-A interface to reduce energy losses, thereby improving the V OC . 39,40 Paper…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cascaded energy level alignments were favorable for efficient charge transfer at the D-A interface to reduce energy losses, thereby improving the V OC . 39,40 Paper…”
Section: Resultsmentioning
confidence: 99%
“…The cascaded energy level alignments should be the main reason for reducing the energy losses. 40 Flexible devices have attracted much attention as a promising power source for wearable electronics. [55][56][57] Here, a conventional device architecture of PET/Ag grids/D-PH1000/PEDOT:PSS/active layer/PDINN/Ag was fabricated.…”
Section: Papermentioning
confidence: 99%
“…As shown in Figure 3c, the n values for the BHJ, PPHJ, and PBHJ devices were determined to be 1.42, 1.54, and 1.26, respectively, which indicate a significant suppression of trapassisted recombination in PBHJ devices. 46,47 As shown in Figure 3d,e, quantitative analysis of the charge lifetime and extraction property in devices was carried out by transient photocurrent (TPC) and transient photovoltage (TPV) decay kinetics characterizations. The TPC measurement was used to investigate the competition between carrier sweep-out and recombination during operation.…”
Section: Charge Transfer Recombination and Excitonmentioning
confidence: 99%
“…In the 650-900 nm region, N3, Qx-p- As shown in Figure S15 (Supporting Information), the energy levels of the D18-Cl, N3, Qx-p-C 7 H 8 O, and Qx-m-C 7 H 8 O have been tested by cyclic voltammetry. [11] In Table S1 Subsequent contact angle test indicated that N3 and two new acceptors should combine well to form composites that approximate alloys in relevant Bhlk heterojunction (BHJ) blend film. [6] Because they possess extremely similar chemical structures.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%